2020
DOI: 10.7717/peerj.9734
|View full text |Cite
|
Sign up to set email alerts
|

Reproductive pattern in the solanum mealybug,Phenacoccus solani: A new perspective

Abstract: Background The reproductive pattern of most scale insects is ovoviviparity. The solanum mealybug, Phenacoccus solani (Hemiptera: Pseudococcidae), is known as a thelytokous parthenogenetic species, but there is still debate about the reproductive strategies of this species. Methods Here, we investigated the oviposition characteristics of P. solani and used scanning/transmission electron microscopy and RNA-seq to identify the differences betw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(15 citation statements)
references
References 48 publications
2
13
0
Order By: Relevance
“…All experiments were conducted under controlled conditions, with a temperature range of 26-28 • C, relative humidity of 70-80%, and a photoperiod of 16 h light and 8 h dark. This environmental setup was based on the method described by Huang et al (2020) [34].…”
Section: Plants and Insectsmentioning
confidence: 99%
See 3 more Smart Citations
“…All experiments were conducted under controlled conditions, with a temperature range of 26-28 • C, relative humidity of 70-80%, and a photoperiod of 16 h light and 8 h dark. This environmental setup was based on the method described by Huang et al (2020) [34].…”
Section: Plants and Insectsmentioning
confidence: 99%
“…Previous studies have shown that AB can successfully switch hosts from PSS to PSI after 6 h of adaptation [34]. Thus, according to our preliminary study, two host switch patterns, the T1 host sequence (PSS-PSI-PSS) and T2 host sequence (PSI-PSS-PSI), were selected to clarify the effect of host switch pattern on the population traits of AB.…”
Section: Effect Of Host Switch Pattern On the Population Traits Of Ae...mentioning
confidence: 99%
See 2 more Smart Citations
“…More than 200 plant species in 55 families in 24 countries around the world are attacked by PSS; it has replaced the cotton bollworm as the main pest of cotton in India and Pakistan (Fand and Suroshe 2015) and poses a great threat to cotton production in China. The solanum mealybug, Phenacoccus solani (Hemiptera: Pseudococcidae) (hereafter PSI), is native to California, North America (Chatzidimitriou et al 2016) and has been newly recorded in China, where it is considered to be a major threat to agricultural production and the ecological environment (Huang et al 2020). Both PSS and PSI belong to the same genus and are invasive in China, but they have different reproductive modes; PSI is a thelytokous parthenogenetic species, with no males in the population (Huang et al 2020), while PSS undergoes only sexual reproduction (Huang et al 2013).…”
Section: Introductionmentioning
confidence: 99%